1992
DOI: 10.3171/jns.1992.77.4.0565
|View full text |Cite
|
Sign up to set email alerts
|

Detection of recurrent gliomas with quantitative thallium-201/technetium-99m HMPAO single-photon emission computerized tomography

Abstract: Deteriorating clinical status after high-dose radiation therapy for high-grade gliomas may be due to radiation changes or may signal recurrent or residual tumor mass. The two conditions cannot be distinguished reliably by computerized tomography (CT) or magnetic resonance (MR) imaging. The authors assessed the ability of sequential thallium-201 chloride (201Tl) and technetium-99m hexamethylpropylene amine oxime (99mTc HMPAO) single-photon emission CT (SPECT) to distinguish tumor recurrence from radiation chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(32 citation statements)
references
References 25 publications
1
29
0
2
Order By: Relevance
“…The present investigation expands these earlier analyses by establishing more detailed correlations of SPECT data with histopathological findings and patient survival time in a large homogeneous population of patients with high-grade astrocytomas. In agreement with preliminary results in previous studies, [5,27] we found that all patients with Tl-201 lesion/scalp ratios greater than 3.5 had high Tc-99m HMPAO uptake (greater than 0.5 that of the cerebellum) as well; these patients (Group III) tended to have highly cellular tumor recurrences on biopsy and had worse survival times at 1 year than all other patients. We further defined a subgroup of patients with Tl-201 uptake ratios between 2 and 3.5 (Group II), which was composed predominantly of patients with less cellular tumor recurrences and with better 1-year survival times (42%) than the patients in Group III (7% 1-year survival); in Groups II and III, Tc-99m HMPAO uptake did not contribute significantly to the results of the analysis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present investigation expands these earlier analyses by establishing more detailed correlations of SPECT data with histopathological findings and patient survival time in a large homogeneous population of patients with high-grade astrocytomas. In agreement with preliminary results in previous studies, [5,27] we found that all patients with Tl-201 lesion/scalp ratios greater than 3.5 had high Tc-99m HMPAO uptake (greater than 0.5 that of the cerebellum) as well; these patients (Group III) tended to have highly cellular tumor recurrences on biopsy and had worse survival times at 1 year than all other patients. We further defined a subgroup of patients with Tl-201 uptake ratios between 2 and 3.5 (Group II), which was composed predominantly of patients with less cellular tumor recurrences and with better 1-year survival times (42%) than the patients in Group III (7% 1-year survival); in Groups II and III, Tc-99m HMPAO uptake did not contribute significantly to the results of the analysis.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that dual-isotope SPECT using Tc-99m HMPAO, a brain perfusion agent that crosses the intact BBB, is more accurate than Tl-201 alone in discriminating radiation changes from recurrence. [5,27,36] The present report correlates the results of dual-isotope SPECT scanning with survival times and histopathological findings in a large population of patients treated with radiotherapy for either an AA or a GBM.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…That study also showed that the ADC ratios in the white matter tracts in the perilesional edema were significantly higher in patients with radiation injury compared with those with recurrent tumor and that the fractional anisotropy (FA) ratios were significantly higher in normal-appearing white matter tracts adjacent to the edema in patients diagnosed with radiation injury compared with those with recurrent tumors. 7 Thallium 201 ( 201 Tl) or 99mTc hexamethylpropyleneamine oxime single-photon emission tomography (HMPAO SPECT) or both [12][13][14] have been reported as useful techniques to discriminate tumor progression and radiation injury. It has been suggested that the combination of lowthallium and low-HMPAO uptake was associated with benign radiation change; whereas increased uptake of either agent or both was associated with recurrent/persistent tumor at biopsy and a poor prognosis.…”
mentioning
confidence: 99%